The interaction of TEA domain transcription factor 4 (TEAD4) and Yes-associated protein 1 (YAP1) promoted the malignant process mediated by serum/glucocorticoid regulated kinase 1 (SGK1). Issue 1 (1st January 2021) - He, Songlin; Zhang, Hanlu; Xiao, Zongwei; Bhushan, Sandeep; Gao, Ke; Wang, Wenping
ABSTRACT: TEA domain transcription factor 4 (TEAD4) has been investigated to be implicated in the progression of various cancers, and it plays a role in the esophageal squamous cell carcinoma (ESCC). The study was designed to investigate how TEAD4 affected the progression of ESCC through Hippo signaling pathway in vitro and in vivo . The interaction of TEAD4 and Yes-associated protein (YAP) was detected though immunoprecipitation assay (IP). Following the treatment of TED-347, which was able to suppress the interaction of TEAD4 and YAP1, the malignant behaviors of cells including proliferation, invasion, and migration were assessed by EDU staining, wound healing, and transwell assay in vitro, while tumor growth was measured. Luciferase reporter plasmids containing the enhancer and promoter region of serum/glucocorticoid regulated kinase 1 (SGK1) were constructed to analyze how TEAD4 affected the transcription of SGK1. The above cell behaviors were further analyzed after the silencing of SGK1. Results showed that TED-347 hindered the promoting effect of TEAD4 overexpression on the malignant behaviors of ESCC cells, and this effect was related to the suppression of the TEAD4/YAP1 complex. Moreover, the promoter activity of SGK1 was obviously inhibited by TED-347. Decreased expression of SGK1 suppressed the above behaviors of cells and destroyed the effects of increased expression of TEAD4. Collectively, TEAD4/YAP promotes the malignant process of ESCC cells, which was inhibited by the interference of SGK1. Targeting TEAD4/YAP1 complex or SGK1 could find application in the treatment of esophageal squamous cell carcinoma. Graphical Abstract: uf0001